2016
DOI: 10.18805/ijar.10992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among meat quality classes according to the criteria ofpost-mortem pH24hr, drip loss and color in Berkshire pigs

Abstract: This study was performed to analyze the difference between the meat properties classified into 5 ranges depending on Berkshire meat quality traits. Post-mortem pH 24hr was positively correlated with water holding capacity, but negatively correlated with meat color, protein content, drip loss, and cooking loss. Berkshire gilt was discovered by higher population of RFN (reddish pink, firm, non-exudative), a normal meat class when compared to barrow, whereas DFD (dark, firm, and dry) was not detected and PSE (pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Canonical correlations measures only correlations between linear combinations of variables rather than direct measurement of correlations between two sets of variables (Kim et al 2016b). Thus, in this work, the numbers of dimension explaining relationships between pork traits were reduced from 13 to 2 by CCA (Fig.…”
Section: Summary Of Canonical Correlation Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Canonical correlations measures only correlations between linear combinations of variables rather than direct measurement of correlations between two sets of variables (Kim et al 2016b). Thus, in this work, the numbers of dimension explaining relationships between pork traits were reduced from 13 to 2 by CCA (Fig.…”
Section: Summary Of Canonical Correlation Analysismentioning
confidence: 84%
“…Canonical correlation analysis (CCA) is a useful multivariate technique for investigation of relationship between sets of independent and dependent variables, which are composed of one or more variables (Sahin et al. 2011;Kim et al, 2016b). Recently, CCA has been performed in livestock field by very few studies (Jaiswal et al, 1995;Mendes and Akkartal, 2007;Kabir et al, 2014), including a simultaneous relationship among breeding efficiency and growth and reproductive trait of buffalo (Thomas and Charkravarty, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the release of adrenaline led to an ante mortem glycogen breakdown and, as a consequence, to a lower pH value [ 47 ]. In addition, the post-mortem pH (24 h) was positively correlated with the water holding capacity, but negatively correlated with the meat color, protein content, drip loss, and cooking loss [ 48 ]. Our findings manifested that all the meat quality parameters measured were no statistically different among the treatments.…”
Section: Discussionmentioning
confidence: 99%